Insostenibilidad de una banda de flotación: un análisis teórico - De La Torre , Carlos (2000)
During the early nineties the "target zones” literature experienced a boom on the basis of Krugman's classic “Target Zones and Exchange Rate Dynamics” (1989). New developments pursued improvements on the original model by introducing more realism to extend its analytical capability. Although the practical application of target zones contributed with empirical experience which entichcd the (heoretical secuence on this line. Such is the Ecuadorian case with lts exchange rate policy applicd since late 1994 to early 1999. Some events experienced during this period, mainly an exchange rate dynamic traspassing the zone and the each time more frequent realignments, surpassed the theoretical establishment of conventional literature. In this sense, this paper develops after the “cannunical” model complete cxplanation an extension which introduces together the possibilities of discrete interventions and non perfect credibility to reinforce the model 's capability for explaining these observed phenomena. Along with these extensions, this paper includes a complementary model which builds an explicit functional relation among the credibility coefficient and agents expected inflation. By the way, an interrclation among targct zones, credibility, and cxpected inflation which 1einforces conventional literature, is proposed.